Annotated translation of the Work of Irish Mythology “The Boyhood of Fionn". - Ycaza Vallarino, Rodrigo Alberto (2018)
The following project consists of the translation into the Spanish language of the medieval Irish folktale The Boyhood of Fionn, as retold by author James Stephens, and a subsequent annotated translation process in which an analysis is provided in order to explain the decisions that were taken when it comes to the rendering of this particular text. This has been accomplished by using translation techniques proposed by English professor of translation Peter Newmark. The decision to work and develop this project was made for two reasons: the first one is to improve personal skills as a translator of fiction by providing the rendering to a work featuring a medieval form of English, which was challenging, as the language used in it features many unfamiliar complexities and the second one is to provide a translation into Spanish of a work that has not been officially translated into this language as of yet. The aforementioned analysis has been done by means of developing extralinguistic charts that feature extracts taken from both versions of the text and comparing them; in the case of the translated version, an explanation of what technique was used to render them into Spanish has been included as a means to provide recommendations for potential translators when having to render texts of this nature.